2020
DOI: 10.1021/acs.organomet.0c00048
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)- and Os(II)-Induced Cycloisomerization of Phenol-Tethered Alkyne for Functional Chromene and Chromone Complexes

Abstract: Diphosphine-containing Ru­(II)/Os­(II)–chromene and −chromone complexes were synthesized from reactions between phenol ynone HCC­(CO)­(o-C6H4OH) and cis-[Ru/Os­(dppm)2Cl2] (dppm = 1,1-bis­(diphenylphosphino)­methane). The structures of these complexes in the solid state along with their pH-dependent chromene/chromone equilibrium behavior in aqueous medium were investigated. The cis–trans equilibration in solution demonstrated by chloride-ligated Ru–chromene and −chromone series represents a rare example for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Although the formation of metal–vinylidene species via alkyne–vinylidene rearrangement has been regarded as a key step in Ru(II)-induced alkyne transformations, a number of our synthetic studies revealed that Ru(II) can also activate alkynes via “non-vinylidene” pathways [ 31 , 32 ]. With the aim to gain control on the modes of alkyne activation, we initiated research activities on probing and isolating intermediates and products from the reactions between functionalized alkynes and a variety of Fe(II), Ru(II) and Os(II) complexes [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In 2015, we reported the synthesis of metallafuran complexes in the form of [M(bpy) 2 (C^O)] + from the reactions between cis -[M(bpy) 2 Cl 2 ] (M = Ru, Os; bpy = 2,2′-bipyridine) and ynone HC≡C(C=O)Ph in MeOH ( Scheme 1 a; C^O represents an anionic bidentate [ C (OMe)CHC(Ph) O ] − chelate, coordinating atoms in italics) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the formation of metal–vinylidene species via alkyne–vinylidene rearrangement has been regarded as a key step in Ru(II)-induced alkyne transformations, a number of our synthetic studies revealed that Ru(II) can also activate alkynes via “non-vinylidene” pathways [ 31 , 32 ]. With the aim to gain control on the modes of alkyne activation, we initiated research activities on probing and isolating intermediates and products from the reactions between functionalized alkynes and a variety of Fe(II), Ru(II) and Os(II) complexes [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In 2015, we reported the synthesis of metallafuran complexes in the form of [M(bpy) 2 (C^O)] + from the reactions between cis -[M(bpy) 2 Cl 2 ] (M = Ru, Os; bpy = 2,2′-bipyridine) and ynone HC≡C(C=O)Ph in MeOH ( Scheme 1 a; C^O represents an anionic bidentate [ C (OMe)CHC(Ph) O ] − chelate, coordinating atoms in italics) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, being a privileged scaffold for drug development due to their biological and pharmacological activities (e.g., anti-inflammatory, antitumor, antimicrobial, and antioxidative properties), [24][25][26][27][28][29][30] the optical properties of chromones offer them new potential applications in fluorescent probes, light-emitting devices, and photochromic materials. [31][32][33] Recently, Han and coworkers reported a metal-free oxidative C-H functionalization of small alkane molecules to prepare 2-alkylchromanones. 34 In view of the mild conditions and high efficiency of this reaction as well as the unique properties of chromones, we adopted this chemistry in the macromolecular realm for polyolefin modification in this report.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently initiated a paradigm in scrutinizing the reactivity between low-valent transition metal precursors and heteroatom-functionalized alkynes [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Gratifyingly, several Ru-and Os-heterocyclic complexes reported by our group exhibit interesting biological applications.…”
Section: Introductionmentioning
confidence: 99%